PRODUKSI BIOENERGI ALTERNATIF DALAM BIODIGESTER MOBILE MELALUI PEMANFAATAN LIMBAH TERNAK SAPI BALI UNTUK MENUNJANG PETERNAKAN BERKELANJUTAN - I.A.G. Widihati; IN. Simpen; N.M. Puspa wati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2013)
The Community Service was conducted in Penglipuran village, involving the cattle breeders of Subak Suka MajuSidewahas. The activity was done initially by intoducing device of biodigester mobile for the place of ferment. Andthen, explaining about potency of feces standard upon which biogas, fermentation teory, technique preparationof raw materials including mixing of feses with water in certain comparison, explaining also the system workbiodigester. Activity phase was continued by demonstration at one of breeder cage. Demonstration started fromphase mixing of feces with water at comparison of 2:3, squealer till put into digester and fermented during 10-15 days. On the day of 16th, it was continued by opening faucet of biodigester for the fella of polutan gas, andthen ignition match to have formed of gas (biogas). The conclusion of this activity showed that the participantwere very enthusiastic attending such valuable activity and manage to form biogas. Biogas which already formedis ready to be interfaced to stove which have been modified. The cattle breeders in Subak Suka Maju Sidewahasalso succeeded to follow technique making of biogas starting from preparing the raw material, perception duringfermentation until the day of 15th production. At last biogas start being used on the day of 20th till the 30th.